KONSEPSI DAN RELEVANSI DOKTRIN ISLAM TENTANG PENDIDIKAN - Iroh Suhiroh,; Wasehudin, (Journal of Innovation Research and Knowledge, 2022)
In fact, the structure of Islamic civilization, from the earliest development of Islam as a whole, derives from the spirit of the Qur'an in addition to the concepts of knowledge contained in the Qur'an. Then this principle is used as Weltanschauung which is the background of human existence globally and is inspired by the era of how the concept of science was defined. The concept of knowledge itself contained in the Qur'an as stated by Ziauddin Sadar is a value which, when well understood from the Islamic frame, will give birth to something about the concept of Islam itself. Islam. In addition, it will also answer its relevance to Islamic religious doctrines. This is worth mentioning in the context of Indonesia's relatively religious society. The method of this writing uses a descriptive analytical method that is normative and philosophical which is adapted to the sources of the literature. This can be understood from the Qur'an which states that God has truly glorified mankind (17:70). In addition, God also clearly asserts that He "deliberately" created humans in different circumstances, with the intention that humans know each other, acknowledge each other's existence, and respect each other